Simplification of Lesson Plan: Elementary School Teacher Perspective: Penyederhanaan Rencana Pelaksanaan Pembelajaran: Perspektif Guru Sekolah Dasar - Vicky Dwi Wicaksono (Pedagogia : Jurnal Pendidikan, 2022)
The policy of simplifying lesson plans as part of the Free Learning Program by the Ministry of Education and Culture has a direct impact on elementary school teachers as drafters of lesson plans. This study aims to find out how teachers view the simplification of the Lesson Plan (RPP) in elementary schools. By using the method of questionnaires and interviews from the point of view of elementary school teachers, it can be found the effectiveness, constraints, and strategies in implementing the new format of lesson plans in elementary schools. The results of the study indicate that the new format of lesson plans can reduce the burden of teacher administrative tasks so that classroom learning becomes more qualified. Elementary school teachers in simplifying thematic lesson plans have their own challenges, combining several subjects into a series of teaching and learning activities into a very simple lesson plan. The strategies that have been carried out by schools to implement this policy are KKG training; peer tutors; and internet sources.